+0  
 
0
193
1
avatar

how to do -4(y+6)=32

Guest Oct 30, 2017

Best Answer 

 #1
avatar+7324 
+1

-4(y + 6) =  32

                             Divide both sides of the equation by  -4 .

y + 6  =  32 / -4

 

y + 6  =  -8

                            Subtract  6  from both sides.

y  =  -8 - 6

 

y  =  -14

hectictar  Oct 30, 2017
 #1
avatar+7324 
+1
Best Answer

-4(y + 6) =  32

                             Divide both sides of the equation by  -4 .

y + 6  =  32 / -4

 

y + 6  =  -8

                            Subtract  6  from both sides.

y  =  -8 - 6

 

y  =  -14

hectictar  Oct 30, 2017

40 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.